2021
DOI: 10.3389/fspas.2020.614018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Latitude-Dependent Gravity Wave Source Variations on the Middle and Upper Atmosphere

Abstract: Atmospheric gravity waves (GWs) are generated in the lower atmosphere by various weather phenomena. They propagate upward, carry energy and momentum to higher altitudes, and appreciably influence the general circulation upon depositing them in the middle and upper atmosphere. We use a three-dimensional first-principle general circulation model (GCM) with implemented nonlinear whole atmosphere GW parameterization to study the global climatology of wave activity and produced effects at altitudes up to the upper … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 104 publications
2
21
0
Order By: Relevance
“…The simulated large wind shear peak varies with the season at middle to high latitudes: higher during winter and lower during summer, consistent with the seasonal variation of the mesopause height. Recently Yiǧit et al (2021) have used the Coupled Middle Atmosphere Thermosphere-2 GCM to study the importance of latitudinal variability in the GW sources for the middle and upper atmosphere. Pedatella and Liu (2018) implemented atmospheric variability into the model study of the atmosphere and ionosphere system to one particular geomagnetic storm.…”
Section: Gravity Wavesmentioning
confidence: 99%
“…The simulated large wind shear peak varies with the season at middle to high latitudes: higher during winter and lower during summer, consistent with the seasonal variation of the mesopause height. Recently Yiǧit et al (2021) have used the Coupled Middle Atmosphere Thermosphere-2 GCM to study the importance of latitudinal variability in the GW sources for the middle and upper atmosphere. Pedatella and Liu (2018) implemented atmospheric variability into the model study of the atmosphere and ionosphere system to one particular geomagnetic storm.…”
Section: Gravity Wavesmentioning
confidence: 99%
“…Whilst the focus of our study is not on the development of the GW parameterization (the focus is rather to provide a detailed decomposition of the migrating and non-migrating modes produced by the ExUM), it is nevertheless pertinent to discuss aspects of the GW parameterization here to aid future development. Particularly in the context of studies such as Ortland and Alexander (2006) and Yigit et al (2021).…”
Section: Migrating Modesmentioning
confidence: 99%
“…It was noted that the overall effects of gravity wave momentum forcing is highly dependent on the chosen gravity wave parameterization and chosen source spectrum. Yigit et al (2021) showed that implementing a latitudinally varying GW source spectrum can have a significant impact on middle atmosphere circulation, which can therefore have an important effect on the diurnal tides.…”
Section: Migrating Modesmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamical and thermodynamical role of GWs in the vertical coupling between the lower and upper atmosphere is being increasingly studied in a global sense in a number of studies (Yiğit et al, 2016, and see the references therein). Numerical models of varying flavors are used to study GW processes in the atmosphere (e.g., Yiğit et al, 2009;Hickey et al, 2011;Heale et al, 2014;Gavrilov and Kshevetskii, 2015;Yiğit et al, 2021). Coarse-grid general circulation models require incorporation of GW models in order to account for subgrid-scale GW and to reproduce the variable and mean structure of the middle and upper atmosphere.…”
Section: Introductionmentioning
confidence: 99%